2022
DOI: 10.1002/ange.202214610
|View full text |Cite
|
Sign up to set email alerts
|

The Single‐Component Flavin Reductase/Flavin‐Dependent Halogenase AetF is a Versatile Catalyst for Selective Bromination and Iodination of Arenes and Olefins**

Abstract: Flavin-dependent halogenases (FDHs) natively catalyze selective halogenation of electron rich aromatic and enolate groups. Nearly all FDHs reported to date require a separate flavin reductase to supply them with FADH 2 , which complicates biocatalysis applications. In this study, we establish that the single component flavin reductase/flavin dependent halogenase AetF catalyzes halogenation of a diverse set of substrates using a commercially available glucose dehydrogenase to drive its halogenase activity. High… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…From our initial report of enantioselective desymmetrization in 2018 38 to recent efforts at atroposelective halogenation 42,54 and enantioselective halocyclization, 45,50,54 the studies outlined above show how FDHs can catalyze enantioselective transformations with diverse structural requirements. This capability is notable since, at least to date, no examples of enantioselective FDH catalysis have been characterized in natural products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From our initial report of enantioselective desymmetrization in 2018 38 to recent efforts at atroposelective halogenation 42,54 and enantioselective halocyclization, 45,50,54 the studies outlined above show how FDHs can catalyze enantioselective transformations with diverse structural requirements. This capability is notable since, at least to date, no examples of enantioselective FDH catalysis have been characterized in natural products.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that the single component flavin reductase/FDH AetF possesses remarkable substrate scope, including relatively electron deficient heterocycles and several substrates that undergo enantioselective transformations. 54 For example, AetF was able to brominate 26 to give 26a in good yield. While low enantioselectivity was observed, this result was notable since our initial desymmetrization study only investigated chlorination of 1.…”
Section: Simplifying and Expanding The Scope Of Asymmetric Fdh Catalysismentioning
confidence: 99%
See 1 more Smart Citation